Combustão iniciada por micro-ondas para a absorção simultânea de metais e halogênios e determinação por ICP-MS, ISE e F AAS - Doneda, Morgana (2016)
In this work, a sample preparation method using microwave-induced combustion (MIC) using a single absorbing solution was applied for further determination of both halogens and metals in biological samples. A whole milk powder sample was used for method evaluation. Fluorine was determined by potentiometry with ion selective electrode (ISE), Cl, Br, I, Ag, Cd, Co, Pb e Sr by inductively coupled plasma mass spectrometry (ICP-MS) and Ca, K, Mg and Na by flame atomic absorption spectroscopy (F AAS). The following parameters were evaluated for MIC: sample mass, nitric acid concentration used as absorbing solution and time of reflux step. According to the results, it was possible to observe that sample masses up to 700 mg were efficiently digested by MIC using 5 mol L-1 HNO3 as absorbing solution an 5 min of reflux. For F determination by ISE, standard solutions were prepared using nitric acid, and the digests, as well standard solutions, were adjusted to pH 5 previous the determination step. For Cl, Br and I determination by ICP-MS, calibration was carried out using 10 mmol L-1 NH4OH solution. Digests were diluted and the pH was adjusted (pH 10), in order to avoid memory effects for I. Losses of I were observed when reflux step was higher than 5 min (10 and 15 min). Digested solutions obtained by using MIC can be stored up to 7 days at 4 °C since no losses of F, Cl, Br and I were observed in this period. It is important to mention that these experiments were not carried out for metals determination. The results obtained by the proposed method (MIC) were in agreement with those obtained by MIC using 25 mmol L-1 NH4OH as absorbing solution for halogens and by microwave-assisted wet digestion (MAWD) using concentrated HNO3 for metals. The accuracy was also evaluated using reference materials (NIST 8435, whole milk powder and NIST 1566a, oyster tissue) and obtained results were in agreement with the reference values. Limits of quantification (LOQs) were lower than 19.2 and 1.8 μg g-1 for halogens and metals determination, respectively. The proposed method was applied to bovine liver and crustaceans samples (Penaeus subtilis and Callichirus major).